Insights into the Chinese Outbound Tourism – An Empirical Analysis. Opportunities for Romania - SARMIZA PENCEA; DANIEL BULIN (Global Economic Observer)
Tourism is a key component of the world economy. Its total contribution to the global growth is considerable, accounting for 9.5% of the overall world GDP in 2013, when it attracted 4.4% of the total world investments it generated one of every 11 new jobs, and about 5.4% of the overall world exports. As it has happened in almost any other industry, a superpower like China has quickly turned into one of the most important players in the international tourism market, leaving an increasingly significant footprint in the field and having an important impact on its development. In this paper the authors intend, on the one hand, to look at China’s swift growth in outbound tourism, and, on the other hand, at Romania’s inbound tourism, trying to identify the ways by which Romania could seize the opportunity of becoming a significant destination for Chinese tourists in Europe and increase its export of tourism services to this country.